The Gas Sensitivity Properties of Nano Ferrite CuxAl0.3-XNi0.7Fe2O4 Synthesized by Sol-Gel Method - Muslim, Tagreed; A. Kadhim , Shaymaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
This study includes the preparation of the ferrite nano ferrite CuxAl0.3-XNi0.7Fe2O4 (where: x = 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3) M using the auto combustion method (sol-gel), and citric acid was used as fuel for auto combustion. The ferrite samples were checked by X-ray diffraction (XRD), Field Emission Scanning Electron Microscopes (FE-SEM), and energy dispersive X-ray analyzer (EDX). They showed that the prepared compound has a face-centered cubic structure (FCC). The lattice constant increases with an increase in the percentage of doping of the copper ions, and a decrease for the aluminum ion and that the compound is porous and its grains are spherical, and there are no other elements other than the elements involved in the preparation of the compound. Which means that it is of high purity. The gas sensing system revealed that the nano ferrite has good sensitivity to hydrogen sulfide (H2S) gas.